«Mi fai fare un giro con la webcam?». Storie di malattia da un’etnografia digitale in Marocco - Zito, Eugenio (EtnoAntropologia, 2022)
In this paper the author, starting from his research in medical anthropology on chronicity in Morocco, discusses, also according to contemporary debate on the anthropology of the web, its extension and re-adaptation digitally, following the limitations imposed on travel by Covid-19 in 2020 and 2021. The difficulties and potential of hybrid ethnography in the digital age, and in the course of a un-precedented so pervasive pandemic as the one we are living, are examined. The illness stories collected remotely with the interlocutors known on fieldwork before the pandemic show some aspects of the recent intense digital acceleration of our social life. Moreover these stories allow on the one hand to critically analyze some methodological aspects connected to digital and hybrid ethnography, and on the other to continue, despite physical distance, the research previously started in presence, albeit some adaptations and methodological updates.